ON CICERO'S FABIUS ARGUMENT. - MARKO, VLADIMÍR (Filozofia, 2020)
This article aims to show that it is impossible to put Cicero's testimonies regarding The Fabius Argument in a consistent inferential order. Either we must suppose that additional premises are tacitly assumed in the text or we must compare it with other sources, which leads to inconsistencies in the proof's reconstruction. Cicero's reconstruction of the progression of the argument has formal shortcomings, and the paper draws attention to some of these deficiencies. He interpreted sources in a revised and intentionally simplified way, with the aim of undermining the views of his opponents, casting them as inconsistent and similar to views held by Diodorus. Rather than being a consistently interpreted argument faithfully transcribed from the Stoic sources, Cicero's Fabius Argument is ultimately anti-Stoic.